IMPROVEMENT OF ADSORPTION EFFICIENCY ON CARBON BLACK DERIVED FROM PLASTIC WASTE PYROLYSIS - Putkham, Apipong; Hanrungcharothon, Suthasini; Saithong, Thanaphun; Putkham, Ajchara Imkum (Life Sciences and Environment Journal, 2021)
In this research, the adsorption characteristics of carbon black derived from municipal plastic waste pyrolysis were improved by both physical and chemical activations methods for improving of surface area. The carbon black was firstly physically treated with various activation temperature and period of carbonization followed by chemically treated with various types and concentrations of chemicals such as sulfuric acid, phosphoric acid, sodium hydroxide and zinc chloride. The iodine adsorption number (IAN) was calculated via iodine titration for indication of adsorption efficiency of the activated carbon black. Furthermore, physical and chemical properties of activated carbon black was characterized by Brunauer-Emmett-Teller, scanning electron microscope/energy dispersive spectroscopy and Fourier transform infrared spectrometry analysis. From experimental results, the suitable condition for activation of carbon black is 400ºC for 15 minutes, followed by impregnation with 20% (w/w) sodium hydroxide for 15 minutes. In comparison with non-activated carbon black, both iodine adsorption number and specific surface area increased from 110.24 to 200.41 mg/g and from 5.45 to 12.63 m2/g, respectively. This is indicated that surface area of the activated carbon black is comparable to the commercial carbon black (11 m2/g).